Inhibiting lung lining fluid glutathione metabolism with GGsTop as a novel treatment for asthma - Tuzova, Marina; Jean, Jyh-Chang; Hughey, Rebecca P.; Brown, Lou Ann S.; Cruikshank, William W.; Hiratake, Jun; Joyce-Brady, Martin (Frontiers in Pharmacology, 2014)
Asthma is characterized by airway inflammation. Inflammation is associated with oxidant stress. Airway epithelial cells are shielded from this stress by a thin layer of lung lining fluid (LLF) which contains an abundance of the antioxidant glutathione. LLF glutathione metabolism is regulated by γ-glutamyl transferase (GGT). Loss of LLF GGT activity in the mutant GGTenu1 mouse causes an increase in baseline LLF glutathione content which is magnified in an IL-13 model of allergic airway inflammation and protective against asthma. Normal mice are susceptible to asthma in this model but can be protected with acivicin, a GGT inhibitor. GGT is a target to treat asthma but acivicin toxicity limits clinical use. GGsTop is a novel GGT inhibitor. GGsTop inhibits LLF GGT activity only when delivered through the airway. In the IL-13 model, mice treated with IL-13 and GGsTop exhibit a lung inflammatory response similar to that of mice treated with IL-13 alone. But mice treated with IL-13 and GGsTop show attenuation of methacholine-stimulated airway hyper-reactivity, inhibition of Muc5ac and Muc5b gene induction, decreased airway epithelial cell mucous accumulation and a 4-fold increase in LLF glutathione content compared to mice treated with IL-13 alone. Mice treated with GGsTop alone are no different from that of mice treated with saline alone, and show no signs of toxicity. GGsTop could represent a valuable pharmacological tool to inhibit LLF GGT activity in pulmonary disease models. The associated increase in LLF glutathione can protect lung airway epithelial cells against oxidant injury associated with inflammation in asthma.